PERANCANGAN STUDIO ANIMASI DI BANJARBARU - Herdhiani, Muhammad Ferza; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The growth of the animation and video film sector was the highest in 2018 at 10.18%. This sector is a new opportunity for animators and VFX artists. Animation creators in South Kalimantan need a place to accommodate their skills in the form of an animation studio. The existence of an animation studio in Banjarbaru, South Kalimantan, opens up job opportunities for graduates of high schools (SMK) who focus on making animations. An animation studio will require a building design that will provide comfort for its users, so the space program needs to be considered and arranged efficiently. The problem raised in the studio design is how to design an animation studio that has an effective relationship between spaces and can provide ideas in the development of stories and the process of making animation? This problem is solved by preparing a space program based on the flow of the animation making work process and differentiating activity zones. The animation studio carries the concept of "Nature Feels" for relaxation and provides a sense of comfort in the work process. This atmosphere can also stimulate ideas in animation making.